Teachers’ Integration of the 21st Century Skills and Lower Primary School Learners’ Acquisition of Collaborative Skills in Thika, Kiambu County Kenya - Wangu Kioko, Serah; Ouko Ongonga, Hudson; Mwaniki, Solomon (CV Media Inti Teknologi, 2025)
Abstract:Background of Study: This study investigated the integration of 21st century skills by Grade Three teachers in lower primary schools and how this influences learners’ acquisition of collaborative learning skills in Thika Subcounty, Kiambu County, Kenya. Collaborative learning is a key component of the Competency-Based Curriculum (CBC), designed to foster communication, critical thinking, and creativity among learners. Aims and Scope of Paper: The paper aimed to examine teachers’ awareness and implementation of 21st century skills, identify challenges in applying CBC-oriented pedagogies, and assess the impact of these practices on learners’ acquisition of corroborative learning skills. Methods: A descriptive research design was employed. Data were collected from 100 purposively selected Grade Three teachers through structured questionnaires, classroom observations, and focused group discussions. Result: Findings revealed that while 78% of teachers were aware of 21st century skills, only 32% consistently applied them in classroom practice. Key barriers included inadequate CBC training, lack of instructional resources, and overcrowded classrooms. Teacher-centered approaches remained predominant, limiting opportunities for effective collaborative learning. Conclusion: Although teachers demonstrated awareness of 21st century skills, their practical application was minimal due to systemic challenges. The study underscores the need for targeted professional development, adequate teaching resources, and supportive structures to strengthen pedagogical practices that enhance collaborative learning in early primary education.